Responses of an In Vitro Coculture Alveolar Model for the Prediction of Respiratory Sensitizers (ALIsens®) Following Exposure to Skin Sensitizers and Non-Sensitizers - Sabina Burla; Aline Chary; Tommaso Serchi; Sébastien Cambier; Kristie Sullivan; Elizabeth Baker; Nikaeta Sadekar; Arno C. Gutleb (Toxics)
In recent years, a global increase in allergy incidence following chemical exposure has been observed. While the process of skin sensitization is well characterized through the adverse outcome pathway (AOP) framework, the immunological mechanisms underlying respiratory sensitization remain less well understood. Respiratory sensitizers are classified as substances of very high concern (SVHC) under the European Union (EU) regulation for the registration, evaluation, authorization and restriction of chemicals (REACH), emphasizing the importance of evaluating respiratory tract sensitization as a critical hazard. However, the existing new approach methodologies (NAMs) for the identification of skin sensitizers lack the capacity to differentiate between skin and respiratory sensitizers. Thus, it is imperative to develop physiologically relevant test systems specifically tailored to assess respiratory sensitizers. This study aimed to evaluate the efficacy of ALIsens®, a three-dimensional (3D) in vitro alveolar model designed for the identification of respiratory sensitizers and to determine its ability to correctly identify sensitizers. In this study, we used a range of skin sensitizers and non-sensitizers to define the optimal exposure dose, identify biomarkers, and establish tentative thresholds for correct sensitizer classification. The results demonstrate that ALIsens® is a promising in vitro complex model that could successfully discriminate respiratory sensitizers from skin sensitizers and non-sensitizers. Furthermore, the thymic stromal lymphopoietin receptor (TSLPr) cell surface marker was confirmed as a reliable biomarker for predicting respiratory sensitization hazards.